2020
DOI: 10.1021/acschemneuro.0c00441
|View full text |Cite
|
Sign up to set email alerts
|

DARK Classics in Chemical Neuroscience: Carfentanil

Abstract: Because of its remarkable potency and relative ease of synthesis, carfentanil (1) has recently emerged as a problematic contaminant in other drugs of abuse. Carfentanil and its close analogues, currently approved only for large animal veterinary medicine, have found use both as illicit additives to the clandestine manufacture of scheduled drugs and as chemical weapons. In this Review, the background, synthesis, manufacture, metabolism, pharmacology, approved indications, dosage, and adverse effects of carfenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 96 publications
0
28
0
Order By: Relevance
“…This recent trend is especially dangerous because the illegal drug user is frequently unaware that they are receiving drugs laced with ultrapotent opioids. Although fentanyl has historically been highlighted as the primary adulterant in the illicit drug supply, carfentanil related overdose deaths rose exponentially between 2016 and 2017 among more than 10 states in the U.S., accounting for approximately 11% of the opioid-related deaths during this time. , Fatalities involving carfentanil are not isolated to the U.S., and cases have been documented in countries across Europe and North America. , Unfortunately, the rise in the number of carfentanil and fentanyl related incidents is placing further strain on already overwhelmed public health systems currently battling a pandemic.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This recent trend is especially dangerous because the illegal drug user is frequently unaware that they are receiving drugs laced with ultrapotent opioids. Although fentanyl has historically been highlighted as the primary adulterant in the illicit drug supply, carfentanil related overdose deaths rose exponentially between 2016 and 2017 among more than 10 states in the U.S., accounting for approximately 11% of the opioid-related deaths during this time. , Fatalities involving carfentanil are not isolated to the U.S., and cases have been documented in countries across Europe and North America. , Unfortunately, the rise in the number of carfentanil and fentanyl related incidents is placing further strain on already overwhelmed public health systems currently battling a pandemic.…”
mentioning
confidence: 99%
“…13,14 Fatalities involving carfentanil are not isolated to the U.S., and cases have been documented in countries across Europe and North America. 12,15 Unfortunately, the rise in the number of carfentanil and fentanyl related incidents is placing further strain on already overwhelmed public health systems currently battling a pandemic.…”
mentioning
confidence: 99%
“…In regards to carfentanil, the predicted metabolite has not yet been reported in vitro or in vivo (Feasel et al ., 2016; Ringuette et al ., 2020). A study with human hepatocytes suggested that ester hydrolysis is probably not a major metabolic pathway for this drug (Feasel et al ., 2016), indicating it is possibly an exclusive microbial product or, at least, a minor human metabolite.…”
Section: Resultsmentioning
confidence: 99%
“… (region D ): alicyclic fragments (e.g., cyclopropyl), linear (elongated) or branched alkyl chains, ether fragments, aromatic fragments (e.g., 2-furanyl). Particularly worth pinpointing seem such interesting analogues as ultrapotent μOR agonists, such as carfentanil ( 1.2 , [ 38 ]) or ohmefentanil ( 1.3 , [ 39 ]), and ultrashort acting analgesics, such as alfentanil ( 1.4 , [ 40 ]) or remifentanil ( 1.5 , [ 41 ]). …”
Section: Introductionmentioning
confidence: 99%
“…Particularly worth pinpointing seem such interesting analogues as ultrapotent μOR agonists, such as carfentanil ( 1.2 , [ 38 ]) or ohmefentanil ( 1.3 , [ 39 ]), and ultrashort acting analgesics, such as alfentanil ( 1.4 , [ 40 ]) or remifentanil ( 1.5 , [ 41 ]).…”
Section: Introductionmentioning
confidence: 99%